Sibling correlations and intergenerational mobility across immigrant groups - Marco Colagrossi; Claudio Deiana; Andrea Geraci; Ludovica Giua; Gianluca Mazzarella (European Commission, 2024)
We study immigrant assimilation in terms of earnings dynamics and patterns of intergenerational transmission in permanent earnings by immigrant generation and neighborhood segregation levels. We estimate comparable sibling correlations across native and immigrant groups, but these seem to be explained by different factors. As immigrants assimilate, their intergenerational transmission mechanisms also become similar to natives. However, less assimilated immigrants experience weaker earnings transmission, a higher persistence of neighborhood effects, and a slower assimilation trajectory.
Keywords: J15; J61; J62; 330; Immigrant assimilation; Sibling correlation; Intergenerational transmission; Segregation